Indonesia's National Zakat Agency (BAZNAS): Digital Transformation in Managing Zakat, Infaq and Shadaqah (ZIS) - Hartono, Haryani Santo (Universitas Islam Internasional Indonesia, 2022)
Indonesia's National Zakat Agency (Badan Amil Zakat Nasional, BAZNAS) is an official government agency that manages the zakat of Indonesian people. BAZNAS is tasked with collecting zakat, infaq, and shadaqah (ZIS) from the community and managing the redistribution of funds to recipients. Through digitalization, BAZNAS has made several breakthroughs towards improving their system management. This is in order to improve the performance of BAZNAS in terms of fundraising and distribution, which have a significant impact on BAZNAS' overall performance. This study aims to describe the transformation of BAZNAS in applying digital technology to management. The author conducted research on BAZNAS for two years, from 2019 to 2020, and found that BAZNAS succeeded in formulating its concept for digitalization even prior to the COVID-19 pandemic. As such, BAZNAS was able to quickly move its programs into the digital realm. Further digitalization is also ongoing at BAZNAS. As Indonesia is the country with the largest number of Muslims in the world, the success of BAZNAS as the national zakat institution in Indonesia can serve as a role model for Muslim communities around the world in ZIS management is a key part of the road towards prosperity in the Muslim world.